Clinopodium eplingianum (Lamiaceae), a new species from Oaxaca, Mexico - González-Gallegos, Jesús Guadalupe; Martorell, Carlos; García-Meza, Diego (Phytotaxa, 2024)
Recent botanical exploration in grasslands in northwestern Oaxaca have revealed a Clinopodium (Lamiaceae) taxon that cannot be referred to any of the current described species. This plant is most similar to C. hintoniorum from northeastern Mexico, in Nuevo Léon, in general habit and architecture; however, it can be easily distinguished by leaf blade shape and width, calyx teeth shape and length, lack of tufts of hairs between them and a distinction in the relative proportion between calyx and corolla tube. This new species represents an addition to the flora of Oaxaca and to the biogeographic province of Sierra Madre del Sur, being endemic to these two areas. The taxon is here presented as C. eplingianum in honor to Carl Epling, the most prominent scholar in the study of American Lamiaceae. Morphological description, distribution map and illustration of the species are provided.